2010 IEEE Frontiers in Education Conference (FIE) 2010
DOI: 10.1109/fie.2010.5673243
|View full text |Cite
|
Sign up to set email alerts
|

Work in progress — Recruiting initiatives for Hispanic, first-generation students

Abstract: The "Program to Increase College Opportunities and Successes" (PICOS) is an NSF S-STEM funded initiative to increase the number of Hispanic, first-generation, economically disadvantaged students in Math, Chemistry, Engineering, and Engineering Technology using scholarship funds and academic success initiatives. The first phase of the project was implementing a recruiting strategy. To facilitate this, a recruiting advisory board composed of Hispanic representatives from the community and university was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A review of papers in the Diversity in Engineering (DinE) bibliography [20] revealed that in the context of diversity, when SES is discussed, authors most often connect it to poor academic performance and attrition. That is, authors note the existence of a generalized, societal-level connection between low SES and low academic achievement, and typically propose an initiative or intervention to help low SES students, often in a K-12 setting and with underrepresented minority populations [e.g., 21,22] . In short, SES tends to be both tacitly and overtly associated with scholarship on K-12, underrepresented minorities, and a lack of academic success and persistence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of papers in the Diversity in Engineering (DinE) bibliography [20] revealed that in the context of diversity, when SES is discussed, authors most often connect it to poor academic performance and attrition. That is, authors note the existence of a generalized, societal-level connection between low SES and low academic achievement, and typically propose an initiative or intervention to help low SES students, often in a K-12 setting and with underrepresented minority populations [e.g., 21,22] . In short, SES tends to be both tacitly and overtly associated with scholarship on K-12, underrepresented minorities, and a lack of academic success and persistence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The program enrolled underclassmen from the TAMUK COE and potential engineering transfer students from nearby community colleges and universities. Extracurricular Bridging Programs identified as a student success strategy by other engineering colleges served as an impetus for the SBP in an NSF IUSE grant [1][2][3]. The intent of this paper is to share the results of the third annual SBP in the NSF IUSE grant implemented at TAMUK, and to inform and solicit feedback from other undergraduate engineering education experts.…”
Section: Introductionmentioning
confidence: 99%
“…The program enrolled underclassmen from the TAMUK COE and potential engineering transfer students from nearby community colleges and universities. Extracurricular Bridging Programs identified as a student success strategy by other engineering colleges served as an impetus for the SBP in an NSF IUSE grant [1][2][3]. The intent of this paper is to share the results of the second annual virtual SBP in the NSF IUSE grant at TAMUK, and to inform and solicit feedback from other undergraduate engineering education experts.…”
Section: Introductionmentioning
confidence: 99%